Celiac Disease in Patients with Cystic Fibrosis-Related Bone Disease. (2nd November 2017) - Putman, Melissa S.; Haagensen, Alexandra; Neuringer, Isabel; Sicilian, Leonard
Abstract : Both cystic fibrosis (CF) and celiac disease can cause low bone mineral density (BMD) and fractures. Celiac disease may occur at a higher frequency in patients with CF than the general population, and symptoms of these conditions may overlap. We report on two patients presenting with CF-related bone disease in the past year who were subsequently found to have concurrent celiac disease. Because adherence to a gluten-free diet may improve BMD in patients with celiac disease, this could have important implications for treatment. Clinicians should consider screening for celiac disease in patients with CF who have low BMD, worsening BMD in the absence of other risk factors, and/or difficult to treat vitamin D deficiency.